Removal of Inorganic Nitrogen by Integrating Seaweed (Sargassum sp.) into Western King Prawn (Penaeus latisulcatus, Kishinouye 1896) Culture - Mai, Huong; Fotedar, Ravi; Fewtrell, Jane (Cuvillier Verlag Göttingen, 2008)
Effluent water from intensive prawn culture ponds typically has high concentrations of dissolved nutrients such as nitrogen. An experiment was conducted for 28 days to investigate the nitrogen flow where seaweed (Sargassum sp.) was integrated into western king prawn (Penaeus latisulcatus) culture. Three treatments were used, each consisting of four, 0.1m3 plastic tanks. Treatment 1 and 2 were the monocultures of western king prawns (5.48 ± 0.29 g) and seaweed (young seaweed). Treatment 3 was an integrated culture of prawns and seaweed. Five prawns were stocked in each tank of treatment 1 and 3. About 137 ± 0.36 g of biomass seaweed was stocked in the treatment 2 and 3. Prawns in prawn monoculture and integrated culture were fed twice a day at a rate of 2.5% of total body weight. The concentration of dissolved inorganic nitrogen (DIN) discharged from the prawn monoculture increased from 0.126 to 10.98 mg/L during the experiment. The concentration of total ammonium nitrogen (TAN), nitrite-nitrogen (NO2-) and nitrate-nitrogen (NO3-) in the integrated culture was significantly lower at the termination of the experiment than the prawn monoculture (p≤0.05). The concentration of TAN, NO2-, NO3- and DIN in the integrated culture remained within non-toxic limits for the duration of the experiment. Integrating Sargassum sp. with prawns did not alter the specific growth rate (SGR) and survival rate of the prawns (p>0.05). The mean biomass of seaweed in the integrated culture increased at the rate of 3.16 ± 0.74% g per day after 7 days of the experiment, which was significantly lower (p≤0.05) than the growth rate of the seaweed in the monoculture (5.70 ± 0.82 % g per day). The results suggest that integrating seaweed into prawn culture can benefit prawn farming by assisting in the maintenance of optimum water quality and thereby, reduce environmental impacts on surrounding areas.